NOVA food groups' consumption associated with nutrient intake profile of school children aged 8-12 years - Arabele Teixeira de Lacerda; Ariene Silva do Carmo; Taciana Maia de Sousa; Luana Caroline dos Santos (Cambridge University Press, 2023)
Abstract Objective: To evaluate the association between the consumption of NOVA food groups (classification based on the nature, extent and purpose of food processing) and the intake of energy, macro and micronutrients among school children. Design: Cross-sectional study. Food consumption was assessed by two 24-h dietary recalls on non-consecutive days. Energy from each NOVA food groups - ultra-processed foods, unprocessed or minimally processed foods, processed culinary ingredients and processed foods - was estimated. For analysis, the percentage of energy from ultra-processed foods and unprocessed or minimally processed foods were categorised into tertiles and associated with intake of energy, macro and micronutrients using analysis of covariance and linear regression. Setting: Public schools in Belo Horizonte, Minas Gerais, Brazil. Participants: School children aged 8-12 years (n 797; 406 girls; 391 boys). Results: Mean energy intake was 2050·18 ± 966·83 kcal/d, 25·8 % was from ultra-processed foods, 56·7 % from unprocessed or minimally processed foods, 8·9 % from processed culinary ingredients and 8·6 % from processed foods. A higher energy contribution from ultra-processed foods was negatively associated with the intake of protein, fibre, vitamin A, Fe and Zn (P < 0·001) and positively associated with total energy, lipid and Na intake (P < 0·001). Concurrently, a higher energy contribution from unprocessed or minimally processed foods was positively associated with the consumption of protein, fibre, Fe and Zn (P < 0·001) and negatively associated with total energy (P = 0·002), lipid and Na intake (P < 0·001). Conclusions: In conclusion, higher ultra-processed food consumption presented a negative association with the nutrient intake profile of school children.